2018
DOI: 10.7150/ntno.22114
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin Detection by Tobacco Mosaic Virus-Assisted Colorimetric Biosensors

Abstract: The presentation of enzymes on viral scaffolds has beneficial effects such as an increased enzyme loading and a prolonged reusability in comparison to conventional immobilization platforms. Here, we used modified tobacco mosaic virus (TMV) nanorods as enzyme carriers in penicillin G detection for the first time. Penicillinase enzymes were conjugated with streptavidin and coupled to TMV rods by use of a bifunctional biotin-linker. Penicillinase-decorated TMV particles were characterized extensively in halochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 74 publications
2
44
0
Order By: Relevance
“…More recently, a novel promising approach for the development of EnEIS biosensors was described in [ 103 , 114 ], where a highly sensitive penicillin biosensor with a superior lifetime was realized by means of modification of a Ta 2 O 5 -gate EIS structure with tobacco mosaic virus (TMV) particles as scaffolds for the dense immobilization of enzymes. The TMV has a nanotube-like structure with an average length of 300 nm, an outer diameter of 18 nm, and an internal channel of 4 nm in diameter [ 115 , 116 ].…”
Section: Chemical Sensors and Biosensors Based On Capacitive Eis Smentioning
confidence: 99%
“…More recently, a novel promising approach for the development of EnEIS biosensors was described in [ 103 , 114 ], where a highly sensitive penicillin biosensor with a superior lifetime was realized by means of modification of a Ta 2 O 5 -gate EIS structure with tobacco mosaic virus (TMV) particles as scaffolds for the dense immobilization of enzymes. The TMV has a nanotube-like structure with an average length of 300 nm, an outer diameter of 18 nm, and an internal channel of 4 nm in diameter [ 115 , 116 ].…”
Section: Chemical Sensors and Biosensors Based On Capacitive Eis Smentioning
confidence: 99%
“…In pioneering works, Wege et al reported that adsorbing GOx-functionalized tobacco mosaic virus nanotubes onto a sensor electrode surface did not actually enhance O2-mediated catalysis, but significantly improved enzyme loading and sensor reusability. [30][31][32] The design of a bioanode bearing a random mesh of M13 bacteriophage particles decorated with GOx has also been reported, but in that case the viral particles were "mineralized" by being gold coated in order to promote direct electron transfer (DET). 33 Using an original immuno-based process, our group previously assembled, a non-integrated GOxbased system on fd bacteriophage particles adsorbed on gold electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…They can be applied to viral nanoparticles before or after their loading with target recognition elements to yield receptor layers of high surface densities, which may increase sensor sensitivity substantially in comparison to conventional layouts. Such "ultradense" presentation of efficiently immobilized capture units by way of plant VLP adapter templates has been demonstrated in several biosensor layouts for distinct systems with both indirect and label-free read-out (e.g., Szuchmacher Blum et al, 2011;Zang et al, 2014Zang et al, , 2017Fan et al, 2015;Koch et al, 2015Koch et al, , 2018aTinazzi et al, 2015;Bäcker et al, 2017;González-Gamboa et al, 2017;Poghossian et al, 2018;Yuste-Calvo et al, 2019b), as also detailed in the respective sections of recent reviews (Koch et al, 2016;Eiben et al, 2019;Benjamin et al, 2020).…”
Section: Plant Virus-enhanced Biosensors: State-of-the Arts and Perspmentioning
confidence: 97%
“…Notwithstanding, we have found only two cases of electrostatic detection of plant virus particles with FEDs. The usability of capacitive field-effect EIS sensors for label-free electrical detection of plant virus particles was initially demonstrated by Koch et al (2018a) and Poghossian et al (2018) for tobacco mosaic virus (TMV). Here, EIS structures with adsorbed TMV particles were used for designing a penicillin biosensor, where the TMV particles served as nanocarriers for enzymes installed at high surface densities on the viral coat protein (CP) subunits.…”
Section: Detection Of Plant Viruses As Pathogens and Potential Model mentioning
confidence: 99%
See 1 more Smart Citation